The Use of Frame Routine Strategies in Reading Comprehension - Wahyuning Murtiyana; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2019)
The objectives of this research are: (1) to find out whether Frame Routine Strategy can improve students’ reading comprehension in class VIII B of SMP Negeri 16 Surakarta in 2018/2019 Academic year, and (2) to describe the class condition when Frame Routine Strategy is implemented in teaching learning process in class VIII B of SMP Negeri 16 Surakarta in 2018/2019 Academic Year. This research used a Classroom Action Research which was implemented in two cycles by using Frame Routine Strategy. The research was conducted in class VIII B of SMP Negeri 16 Surakarta. The object of this research was students on class VIII B, the total number of the students was 32 students which consisted of 14 males and 18 females. Each cycle consisted of two meetings which contained of some activities: identifying the problem, planning the action, implementing the action, observing, reflecting and revising the plan. In collecting the data, the researcher used interview, observation, documentation, and test. In analyzing the data, the researcher used qualitative and quantitative data analyses. Based on the result of this research, the mean score of the students in pre-test was 49,63, meanwhile in the post- test 1 of cycle , it increased to 61,18. In the post-test 2 of cycle 2, it increased to the average value 77,69. It showed that the mean score of post-test 1 was still lower than the minimum score (73). Meanwhile, the mean score of post-test 2 was higher than the minimum score (73). Besides, in class condition, the students were motivated and fun in reading comprehension using Frame Routine Strategy. Based on the research finding, it could be concluded that the Frame Routine Strategy can improve students’ reading comprehension. Further, this strategy is suggested to be used by the teachers in teaching and learning reading in order to be more creative and innovative. The students are suggested to apply it, so that it can help them to be more confidence and fun in learning English. The other resercher who will conduct the same strategy can learn and explore more creative on how this strategy improves students’ reading comprehension. Keywords : Reading Comprehension, Frame Routine Strategy, Classroom Action Research